Functional effects of castration on alpha(1)-adrenoceptors in rat vas deferens - Pupo, A. S. (Elsevier B.V., 1998)
The effects of castration on alpha(1)-adrenoceptors in rat vas deferens were investigated by determining the actions of selective antagonists against the contractions induced by noradrenaline. The results obtained in vas deferens from control rats suggest participation of alpha(1A)-adrenoceptors as judged by the pA(2) values for prazosin (9.6), benoxathian (9.5), 2(2,6-dimethoxyphenoxyethyl) amino-methyl-1,4-benzodioxone hydrochloride) (WB 4101) (9.6), phentolamine (8.4), 8-[2-[4-(2-methoxyphenyl)-1-piperazinyl]ethyl]-8-azaspiro[4.5] decane-7,9-dionedihydrochloride (BMY 7378) (6.7) and by the insensitivity to chloroethylclonidine (100 mu M, 45 min). In vas deferens from castrated rats, WE 4101 and spiperone showed slopes lower than 1.0 in the Schild plots, suggesting participation of multiple receptors. In these organs, noradrenaline contractions were partially inhibited by chloroethylclonidine (100 mu M, 45 min), indicating participation of alpha(1B)-adrenoceptors. After chloroethylclonidine treatment, WE 4101 showed a slope not different from 1.0 in the Schild plot, resulting in a pA(2) of 9.4, which indicates an interaction with alpha(1A)-adrenoceptors. It is suggested that castration modifies the functional alpha(1)-adrenoceptors subtypes in rat vas deferens. (C) 1998 Elsevier B.V. B.V. All rights reserved.
Keywords: vas deferens; alpha(1)-adrenoceptor; castration